Ontologia do ser social : desigualdades e precarização do acesso à educação em tempos de pandemia da COVID-19 (2020-2022) - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The Covid-19 pandemic crisis shook world society and led us to seek information in different directions, particularly with a view to observing its effects in the educational field. In this sense, we seek information about the theme related to the development of school training activities in Basic Education in our country. Such information from official documents and information and communication vehicles enabled us to investigate the transformations that involved part of educational activities in our country. The abrupt social isolation, the suspension of face-to-face classes and the adoption of remote classes completely transformed the daily reality of students, parents and teachers. The first objective of this work refers to the investigation of the right of access to education in times of a pandemic, considering the power relations established within capitalist society. We are guided by an analytical approach to the historical context in times of a pandemic, as we understand that it can provide the reading of elements that represent the Brazilian public educational reality due to its precariousness. The methodological procedures led to a bibliographic review that allowed us the theoretical basis for our assumptions, in view of the analysis of external and internal factors, followed by an exploratory, descriptive and explanatory research. We clarify that our direction for documentary research is characterized by the search for information in written records, which are used as a source of knowledge. The information collected in the first phase of the research had the purpose of investigating the aspects caused by the pandemic in the educational sphere in our country and in the municipality of Caldas Novas/GO. We use a Marxist theoretical foundation because according to our initial surveys, we found a lack of material and immaterial resources for the population with low purchasing power (subaltern classes) to keep their children in school, as they did not have the necessary technological resources and equipment to follow classes and learning activities remotely.
Ontology of the social being : inequalities and precarious access to education in times of the Covid-19 Pandemic (2020-2022)
Keywords: Educação a distância; Ensino remoto; COVID-19; Classes subalternas; Distance education; Remote learning; Subaltern classes; EDUCACAO::ENSINO-APRENDIZAGEM; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO PRE-ESCOLAR; PLANEJAMENTO E AVALIACAO EDUCACIONAL::PLANEJAMENTO EDUCACIONAL